Design, construction and evaluation of the CSU optical fog detector - Emert, Scott E., author; Collett, Jeffrey L., Jr., author (Colorado State University. Libraries, 2001)
The goal of this project was to develop an inexpensive cloud/fog detector that could be used to automate sampling equipment at remote (unmanned) cloud/fog research sites. A secondary objective was to test the ability of this sensor to measure/track trends in fog/cloud liquid water content (LWC). This characteristic is important because LWC is a significant indicator of a cloud's ability to process aerosols and gases and changes in LWC often correspond to changes in fog/cloud solute concentration. The following actions were taken to help realize these objectives. An evaluation of the use of commercially available optical components for fog detection has been performed. The research reinforced the need to have an inexpensive cloud/fog detector that could be used to automate sampling equipment at remote (unmanned) cloud/fog research sites. No such instrument is currently available commercially. Requirements for components of the CSU Optical Fog Detector (OFD) were defined. Important factors included transmitter wavelength and modulation characteristics, detector sensitivity, and component stability/durability over a range of environmental conditions. Readily available commercial components were utilized to ensure the sensor could be built economically. Laboratory tests in a glove box filled with artificially generated fog proved that optical components purchased from Banner Engineering were capable of monitoring changes in fog liquid water content (L WC) when operated in a light attenuation mode. After an initial calibration, the signal from the CSU OFD was found to correlate strongly with LWC measured by a Gerber Scientific Particulate Volume Monitor (PVM-100). Theoretical calculations of attenuation of 880 run light passing through a population of fog drops were completed. The results indicated extinction decreases as the drops are shifted to larger sizes (with a fixed LWC and lognormal distribution breadth). Accordingly, the response of the CSU OFD is expected to vary with mean fog/cloud drop size. Numerous fog detector design configurations were tested and the current attenuation design of the CSU optical fog detector was deemed successful in that it provides, at a minimum, an inexpensive switch capable of automating remote fog sensing equipment. It also provides useful information concerning fog LWC. Two calibrated OFD's were compared to PVM LWC measurements during initial field tests of orographic clouds at Storm Peak Laboratory (SPL) in Steamboat Springs, Colorado. The combined results from both OFD's overall time periods yield a regression equation of LWCofd = 0.99 * LWCpvm with a correlation coefficient of 0.92. Tests performed in the absence of fog on top of our laboratory in Fort Collins provided a measure of OFD baseline noise. Analysis of the observed noise yielded a minimum detection limit of 4.4 mg m·3 for the OFD and a comparable value (5.6 mg m·3) for the PVM. The OFD was incorporated in several automated fog sampling systems deployed in California's San Joaquin Valley as part of the California Regional Particulate Air Quality Study (CRP AQS). The OFD performed well as a fog detector and provided some insight into fog LWC. LWC measurements by a PVM and a co-located OFD showed good correlation (R2 = 0.91) and only modest bias (LWCofd = 1.16 LWCpvm) during an extended radiation fog episode.
July 2001.
Also issued as Scott E. Emert's thesis (M.S.) -- Colorado State University, 2001.
Keywords: Clouds -- Remote sensing; Fog -- Remote sensing; Atmosphere -- Remote sensing